2021
DOI: 10.1038/s41434-021-00282-6
|View full text |Cite
|
Sign up to set email alerts
|

Non-viral delivery of CRISPR–Cas9 complexes for targeted gene editing via a polymer delivery system

Abstract: Recent advances in molecular biology have led to the CRISPR revolution, but the lack of an efficient and safe delivery system into cells and tissues continues to hinder clinical translation of CRISPR approaches. Polymeric vectors offer an attractive alternative to viruses as delivery vectors due to their large packaging capacity and safety profile. In this paper, we have demonstrated the potential use of a highly branched poly(β-amino ester) polymer, HPAE-EB, to enable genomic editing via CRISPRCas9-targeted g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 70 publications
1
31
0
Order By: Relevance
“…Lastly, we have shown that PMBN enhanced electrotransformation can be used to optimise the delivery of DNA–protein complexes (e.g. for TIS library construction) and we expect that this could also potentially be extended to developing a delivery system for ribonucleoprotein (RNP)-mediated CRISPR genome editing 29 in bacterial cells for efficient targeted mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we have shown that PMBN enhanced electrotransformation can be used to optimise the delivery of DNA–protein complexes (e.g. for TIS library construction) and we expect that this could also potentially be extended to developing a delivery system for ribonucleoprotein (RNP)-mediated CRISPR genome editing 29 in bacterial cells for efficient targeted mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, we have shown that PMBN enhanced electrotransformation can be used to optimise the delivery of DNA-protein complexes (e.g. for TIS library construction) and we expect that this could also potentially be extended to developing a delivery system for ribonucleoprotein (RNP)-mediated CRISPR genome editing 29 in bacterial cells for e cient targeted mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Other advantages of the non-viral vectors would be the ease of production, thereby, cost-effectiveness, and their ability to be engineered ( Ramamoorth and Narvekar, 2015 ). On top of that, non-viral vectors can transfer bigger sizes of nucleic acid residues and/or proteins ( Morrell et al, 2008 ; Chang et al, 2017 ; Lee et al, 2018 ; Park et al, 2019 ; Zhang et al, 2021 ; Jubair et al, 2021 ; O'Keeffe Ahern et al, 2022 ). Considering the current progress in gene editing technology, transferring larger biomolecule complexes is desired.…”
Section: Non-viral Vector-mediated Gene Deliverymentioning
confidence: 99%